The positive thinking skills scale: Validity and reliability evidence among Spanish speaking college students in Costa Rica - Garnier Villarreal, Mauricio (2023)
Identifying depressive cognitions in Spanish speaking college students can be vital to prevent the development of clinical depression. This study examines the cross-cultural equivalence as well as the reliability and the validity of the Spanish version of the Positive Thinking Skills Scale (SPTSS) among 286 Spanish speaking college students. The data analysis was done using Structural Equation Modeling, with the R package lavaan. The results provide solid support for the scale’s reliability and validity among Spanish speaking college students as demonstrated by high ordinal α of 0.904 and McDonald ω of 0.859. The findings of the study provide evidence of the construct validity of the (S-PTSS) as indicated by a negative correlation with both Anxiety (r = -0.384) and Loneliness (r = -0.508). The S-PTSS is a useful screening tool for depressive cognition among Spanish speaking college students.